2021
DOI: 10.3390/en14164747
|View full text |Cite
|
Sign up to set email alerts
|

Real Driving Emissions—Conception of a Data-Driven Calibration Methodology for Hybrid Powertrains Combining Statistical Analysis and Virtual Calibration Platforms

Abstract: The combination of different propulsion and energy storage systems for hybrid vehicles is changing the focus in the field of powertrain calibration. Shorter time-to-market as well as stricter legal requirements regarding the validation of Real Driving Emissions (RDE) require the adaptation of current procedures and the implementation of new technologies in the powertrain development process. In order to achieve highest efficiencies and lowest pollutant emissions at the same time, the layout and calibration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…However, the differences in the experimental and simulation results in the road test were 10% for fuel consumption, 9% for HC emissions, 24% for CO emissions, and 6% for NOx emissions. Krysmon et al [18] created software that, together with a hardware-in-the-loop (HiL) station, made it possible to simulate RDE tests, mainly of hybrid drive systems. The test results outlined in the paper showed that the calibration process was shortened by 20% and, at the same time, 98% compliance was achieved in exhaust emissions and fuel consumption.…”
Section: Parameter Euro 6dmentioning
confidence: 99%
“…However, the differences in the experimental and simulation results in the road test were 10% for fuel consumption, 9% for HC emissions, 24% for CO emissions, and 6% for NOx emissions. Krysmon et al [18] created software that, together with a hardware-in-the-loop (HiL) station, made it possible to simulate RDE tests, mainly of hybrid drive systems. The test results outlined in the paper showed that the calibration process was shortened by 20% and, at the same time, 98% compliance was achieved in exhaust emissions and fuel consumption.…”
Section: Parameter Euro 6dmentioning
confidence: 99%
“…10,[109][110][111] The use of Real Driving Emissions (RDE) testing makes emissions testing more complex, and VIL has been proposed as a way to replicate real-world conditions in a test rig. 112 Additional challenges exist for the testing of all-wheel drive vehicles. 113…”
Section: Vehilmentioning
confidence: 99%
“…Additionally, advanced methods are being developed to ensure emission robustness and compliance up to the full useful life of the exhaust aftertreatment system (EATS) [6,13]. State of the art strategies ensuring RDE compliance have also been developed to cope with the broad and comprehensive test matrix required to effectively cover all possible RDE scenarios [14][15][16][17]. Hence, the ultimate goal is the zero impact emission vehicle, such as investigated by Maurer et al and Boger et al [1,18].…”
Section: Introduction 1motivationmentioning
confidence: 99%